Point-of-care ultrasound in pre-bronchoscopy assessment of acute dyspnea: A case of concurrent massive pulmonary embolism and deep vein thrombosis - Mohammad Amirul Shahril Ahmad; Larry Ellee Nyanti; Jie Cong Yeoh; Hing, Chan Tha A; Chai, Chan Sin; Tie, Siew Teck (Wiley-Blackwell Publishing Ltd, 2022)
Point-of-care ultrasound (POCUS) leads to efficient real-time diagnosis in a wide range of medical specialties. We describe the use of cardiac, lung and lower limb POCUS to rapidly diagnose massive pulmonary embolism and deep vein thrombosis in a 64-year-old patient presenting with acute dyspnea prior to elective bronchoscopy. Left femoral vein thrombus and features of increased right heart pressure on POCUS led to the decision to administer fibrinolytic therapy, with subsequent CT pulmonary angiogram confirming bilateral PE. The use of POCUS allowed for rapid imaging and interpretation leading to a rapid diagnosis of PE, thus fast-tracking lifesaving anticoagulation, especially in an outpatient setting.